2012
DOI: 10.1002/asia.201200881
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Zwitterions: Enhanced Binding and Selective Recognition of Miltefosine by a Squaramide‐Based Host

Abstract: The importance of a synergic combination between electrostatic and hydrogen‐bonding interactions has been demonstrated. A self‐complementary amidosquarate‐squaramide host for miltefosine has been disclosed. In DMSO, this rather structurally simple host exhibits high affinity and enhanced selectivity for miltefosine owing to the goal‐keeping effect of the amidosquarate unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Squaramides are excellent molecular recognition units due their capacity to establish cooperative hydrogen bonds. The combination of squaramide moieties with tetralkylammonium groups has led to hosts that strongly bind oxoanions, such as phosphate, sulfate, and carboxylate, in water–ethanol mixtures. All these features suggested that squaramide-based compounds could internalize into the cell, mimicking the CPP’s performance. With the aim to investigate the cellular uptake and trafficking within the cell of cylosquaramide compounds, we have prepared the cyclosquaramide fluorescent probes 1 and 2 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Squaramides are excellent molecular recognition units due their capacity to establish cooperative hydrogen bonds. The combination of squaramide moieties with tetralkylammonium groups has led to hosts that strongly bind oxoanions, such as phosphate, sulfate, and carboxylate, in water–ethanol mixtures. All these features suggested that squaramide-based compounds could internalize into the cell, mimicking the CPP’s performance. With the aim to investigate the cellular uptake and trafficking within the cell of cylosquaramide compounds, we have prepared the cyclosquaramide fluorescent probes 1 and 2 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Costa and co-workers reported a self-complementary amidosquarate-squaramide host for miltefosine 103 (Figure 32). 88 The authors exploited the charged amidosquarate unit as the binding site for the cationic quaternary amine of miltefosine and a neutral squaramide unit, located at a precise distance away to act as a binding site for the anionic phosphate. The combination of two different squaramide units effectively enhanced the affinity and selectivity for miltefosine by using a structurally simple receptor.…”
Section: Somentioning
confidence: 99%
“…Lately different scaffolds used in zwitterion recognition have been described: Costa published a receptor based on bis‐squaramides; the group of Moran has published different molecular receptors for the formation of non‐polar host‐guest complexes including a system based in a benzofuran skeleton and two pyridine molecules attached as sulfonamide and carboxamide groups or a receptor based on a chiral chromane . A choline phosphate receptor based on a tripodal hexa‐urea scaffold functionalized with aromatic terminal groups 21 was described by Yang and Wu .…”
Section: Miscellaneous Receptorsmentioning
confidence: 99%